2023
DOI: 10.1101/2023.01.16.524164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EEF2-inactivating toxins engage the NLRP1 inflammasome and promote epithelial barrier disruption uponPseudomonasinfection

Abstract: The intracellular inflammasome complex have been implicated in the maladaptive tissue damage and inflammation observed in chronic Pseudomonas aeruginosa infection. Human airway and corneal epithelial cells, which are critically altered during chronic infections mediated by P. aeruginosa, specifically express the inflammasome sensor NLRP1. Here, together with a companion study, we report that the NLRP1 inflammasome detects Exotoxin A (EXOA), a ribotoxin released by P. aeruginosa Type 2 Secretion System (T2SS) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…[184] show that human NLRP1 is cleaved at the Q333 site by multiple coronavirus 3CL proteases, triggering inflammasome assembly and cell death. The same group also shows IL‐1 secretion and hypersensitivity to Exotoxin A from Pseudomonas aeruginosa through ribotoxic stress‐dependent NLRP1 inflammasome activation in nasal epithelial cells obtained from Cystic Fibrosis patients [155]. These observations connect NLRP1 to the deleterious effects of P. aeruginosa infections of Cystic Fibrosis patients and could also extend to patients with Chronic Obstructive Pulmonary Disease and their increased pulmonary inflammation and epithelial disruption.…”
Section: Respiratory Tract Epithelial Cellsmentioning
confidence: 89%
See 1 more Smart Citation
“…[184] show that human NLRP1 is cleaved at the Q333 site by multiple coronavirus 3CL proteases, triggering inflammasome assembly and cell death. The same group also shows IL‐1 secretion and hypersensitivity to Exotoxin A from Pseudomonas aeruginosa through ribotoxic stress‐dependent NLRP1 inflammasome activation in nasal epithelial cells obtained from Cystic Fibrosis patients [155]. These observations connect NLRP1 to the deleterious effects of P. aeruginosa infections of Cystic Fibrosis patients and could also extend to patients with Chronic Obstructive Pulmonary Disease and their increased pulmonary inflammation and epithelial disruption.…”
Section: Respiratory Tract Epithelial Cellsmentioning
confidence: 89%
“…Once ZAKa is activated, it auto-phosphorylates itself and phosphorylates NLRP1 and MAPKs p38 and c-Jun N-terminal kinase (JNK) and downstream proteins involved in apoptosis and inflammation [151,152]. More recently, bacterial toxins, dsRNA and the NLRP3 agonist nigericin are shown to induce NLRP1 activation through ribosome stalling and activation of the ZAKa/p38 pathway, suggesting that targeting this pathway may serve as a target for a broad spectrum of diseases [154][155][156][157][158][159]. More recently, cytosolic peptide accumulation in combination with reductive stress was found to strongly activate NLRP1 activation.…”
Section: Mechanisms Of Inflammasome Activationmentioning
confidence: 99%
“…However, unlike NLRP3, activated NLRP1 localizes almost exclusively to ASC specks and not to any obvious organellar or endosomal structures (Figure 1C). Recently, we and others reported that NLRP1 can be activated by the ribotoxic stress response kinase ZAKɑ downstream of ribosome stalling and/or collisions [26][27][28][29] . This discovery explains why NLRP1 can sense seemingly unrelated triggers, including UVB irradiation, small molecule ribosome inhibitors such as ANS and at least three known bacterial exotoxins.…”
Section: Nigericin Blocks Protein Synthesis and Induces Ribotoxic Str...mentioning
confidence: 99%
“…Robinson et al identified that bacterial exotoxins including Diphtheria toxin from Corynebactetrium diphtheriae, Exotoxin A from Pseudomonas aeruginosa, and sidl from Legionella pneumophila that target the human ribosome elongation factors EEF1 and EEF2, inducing ZAKα, p38, and JNKs; triggering NLRP1-dependent pyroptosis in human keratinocytes 42 . Further complementing these studies, Pinilla et al also describe ExoA, Diphtheria toxin, and Cholix toxin from Vibrio cholerae as targeting EFF2 to induce NLRP1 activity via ribotoxic stress and ZAKα/p38 in primary human corneal, nasal epithelial cells and the human alveolar epithelial cell line A549 43 , further developing the concept that NLRP1 is a critical sensor of cellular stress in non-myeloid cells such as keratinocytes, corneal and airway epithelial cells. Importantly in relation to disease pathogenesis, Pinilla and colleagues also described exacerbated p38 activity and IL-1β secretion and hypersensitivity to ExoA-induced ribotoxic stress-dependent NLRP1 inflammasome activation in nasal epithelial cells obtained from Cystic Fibrosis patients.…”
mentioning
confidence: 93%